Delayed Neurosurgical Intervention in Traumatic Brain Injury Patients Referred From Primary Hospitals Is Not Associated With an Unfavorable Outcome - Grevfors, Niklas; Lindblad, Caroline; Nelson, David W.; Svensson, Mikael; Thelin, Eric Peter; Rubenson Wahlin, Rebecka (Frontiers in Neurology, 2021)
Background: Secondary transports of patients suffering from traumatic brain injury (TBI) may result in a delayed management and neurosurgical intervention, which is potentially detrimental. The aim of this study was to study the effect of triaging and delayed transfers on outcome, specifically studying time to diagnostics and neurosurgical management. Methods: This was a retrospective observational cohort study of TBI patients in need of neurosurgical care, 15 years and older, in the Stockholm Region, Sweden, from 2008 throughout 2014. Data was collected from pre-hospital and in-hospital charts. Known TBI outcome predictors, including the protein biomarker of brain injury S100B, were used to assess injury severity. Characteristics and outcomes of direct trauma center (TC) and that of secondary transfers were evaluated and compared. Functional outcome, using the Glasgow Outcome Scale, was assessed in survivors at 6-12 months after trauma. Regression models, including propensity score balanced models, were used for endpoint assessment. Results: A total of n=457 TBI patients were included, n=320 (70%) patients were direct TC transfers, while n=137 (30%) were secondary referrals. In all, n=295 required neurosurgery the first 24 hours after trauma (about 75% of each sub-group). Direct TC transfers were more severely injured (median GCS 8 vs 13) and more often suffered a high energy trauma (31% vs 2.9%) as compared to the secondary referrals. Admission S100B was higher in the TC transfer group, though S100B levels 12-36h after trauma were similar between cohorts. Direct or indirect TC transfer could be predicted using propensity scoring. The secondary referrals had a shorter distance to the primary hospital, but had later radiology and surgery compared with the TC group (all p<0.001). In adjusted multivariable analyses with and without propensity matching, direct or secondary transfers were not found significantly related to outcome. Time from trauma to surgery did not affect outcome. Conclusions: TBI patients secondary transported to a TC had surgical intervention performed hours later, though this did not affect outcome, presumably demonstrating that accurate pre-hospital triaging was performed. This indicates that for selected patients, a wait-and-see approach with delayed neurosurgical intervention is not necessarily detrimental, but warrants further research.